2013
DOI: 10.1017/s0033291713001396
|View full text |Cite
|
Sign up to set email alerts
|

DSM-IV defined conduct disorder and oppositional defiant disorder: an investigation of shared liability in female twins

Abstract: Background DSM-IV specifies a hierarchal diagnostic structure such that an ODD diagnosis is applied only if criteria are not met for CD. Genetic studies of ODD and CD support a combination of shared genetic and environmental influences, but largely ignore the imposed diagnostic structure. Methods We examined whether ODD and CD share an underlying etiology while accounting for DSM-IV diagnostic specifications. Data from 1446 female twin pairs, aged 11–19, were fitted to two-stage models adhering to the DSM-IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
(86 reference statements)
1
8
0
Order By: Relevance
“…In line with previous research, we found that the overlap between ADHD-like and externalizing traits was largely explained by shared genetic factors (Dick et al, 2005; Knopik et al, 2013; Nadder et al, 2002; Tuvblad et al, 2009). Particularly, one study has shown that the covariation between the two traits across time is governed by genetics (Nadder et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous research, we found that the overlap between ADHD-like and externalizing traits was largely explained by shared genetic factors (Dick et al, 2005; Knopik et al, 2013; Nadder et al, 2002; Tuvblad et al, 2009). Particularly, one study has shown that the covariation between the two traits across time is governed by genetics (Nadder et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…There is also evidence that the overlap between ADHD-like and externalizing traits, such as ODD and CD symptoms, are mainly of genetic origin (Dick, Viken, Kaprio, Pulkkinen, & Rose, 2005; Knopik et al, 2013; Nadder, Rutter, Silberg, Maes, & Eaves, 2002; Tuvblad, Zheng, Raine, & Baker, 2009); however, not all studies have reached that conclusion (Burt, Krueger, McGue, & Iacono, 2001). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High scores on the CBCL externalizing behavior scale may, however, point to comorbid disorders and phenotypic dimensions, such as oppositional defiant disorder (ODD), conduct disorder (CD) or irritability, the overlap of which being largely explained by shared genetic factors (Dick et al, 2005;Knopik et al, 2014;Kuja-Halkola et al, 2014;Tuvblad et al, 2009). Also, recent studies have emphasized the importance of pleiotropic effects of genetic risk variants of psychiatric disorders (CrossDisorder Group of the Psychiatric Genomics Consortium, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Family studies have found that ADHD and DBDs have distinct genetic architectures with moderate to high genetic overlap in the range of 0.34 -0.74 23,24,25 . The existence of genetic risk factors specific to the aggressive and disruptive component of ADHD+DBDs finds support from a twin study where DBDs had an estimated heritability of 0.33-0.64 after controlling for ADHD, with a significant genetic component also observed for DBDs in individuals without ADHD 26 .…”
Section: Introductionmentioning
confidence: 94%